2008
DOI: 10.1017/s000711450802504x
|View full text |Cite
|
Sign up to set email alerts
|

Consumption of mate tea (Ilex paraguariensis) decreases the oxidation of unsaturated fatty acids in mouse liver

Abstract: Mate (Ilex paraguariensis) is rich in polyphenolic compounds, which are thought to contribute to the health benefits of tea. Mate tea was administered orally to mice at a dose of 0·5, 1·0 or 2·0 g/kg for 60 d, and changes both in serum lipid concentration and fatty acid composition of liver and kidney were examined. The effects of mate tea on serum and tissue lipid peroxidation were assessed by the evaluation of thiobarbituric acidreactive substances (TBARS). In tea-consuming mice, both MUFA (18 : 1n-9) and PU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 29 publications
1
27
0
2
Order By: Relevance
“…Yerba mate extracts have been previously shown to provide antioxidant activity and inhibition of low-densitylipoproteins oxidation (Gugliucci and Stahl, 1995;Filip et al, 2000;Chandra and De Mejia Gonzalez, 2004) in vitro (Gugliucci and Stahl, 1995;Filip et al, 2000) and in vivo (Gugliucci, 1996;Schinella et al, 2000;Lanzetti et al, 2008). Similarly, Martins et al (2009) determined that mice fed yerba mate had lower thiobarbituric acid reactive substances in the liver, suggesting that treatment with yerba mate extract protected unsaturated fatty acids from oxidation and may especially protect the liver (Martins et al, 2009).…”
Section: Antioxidant Anti-obesity Anti-inflammationmentioning
confidence: 94%
“…Yerba mate extracts have been previously shown to provide antioxidant activity and inhibition of low-densitylipoproteins oxidation (Gugliucci and Stahl, 1995;Filip et al, 2000;Chandra and De Mejia Gonzalez, 2004) in vitro (Gugliucci and Stahl, 1995;Filip et al, 2000) and in vivo (Gugliucci, 1996;Schinella et al, 2000;Lanzetti et al, 2008). Similarly, Martins et al (2009) determined that mice fed yerba mate had lower thiobarbituric acid reactive substances in the liver, suggesting that treatment with yerba mate extract protected unsaturated fatty acids from oxidation and may especially protect the liver (Martins et al, 2009).…”
Section: Antioxidant Anti-obesity Anti-inflammationmentioning
confidence: 94%
“…13,14 The present authors recently reported that mate tea was able to protect unsaturated fatty acids from oxidation and decrease DNA damage in the liver of mice. 15,16 It also presents a hypocholesterolemic effect, which is associated with the inhibition of pancreatic lipase activity. 17 Other biological effects such as chemopreventive activity, 18,19 choleretic effect, 20 vasodilatation effect, 21 inhibition of glycation, 22 and anti-atherosclerotic properties 23 were also reported.…”
Section: Research Articlementioning
confidence: 99%
“…The species has high nutritional value, particularly antioxidant properties, which is important to maintain human health. [1][2][3][4] Color, flavor, and fragrance are the principal quality attributes of yerba mate, [5] all of which are influenced by moisture content. Therefore, moisture control and monitoring are necessary in the production chain to prevent the growth of spoilage microorganisms and lengthen the storage period.…”
Section: Introductionmentioning
confidence: 99%